2016
DOI: 10.1111/desc.12425
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver talk to young Spanish‐English bilinguals: comparing direct observation and parent‐report measures of dual‐language exposure

Abstract: In research on language development by bilingual children, the early language environment is commonly characterized in terms of the relative amount of exposure a child gets to each language based on parent report. Little is known about how absolute measures of child-directed speech in two languages relate to language growth. In this study of 3-year-old Spanish-English bilinguals (n = 18), traditional parent-report estimates of exposure were compared to measures of the number of Spanish and English words childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
102
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(134 citation statements)
references
References 38 publications
9
102
0
Order By: Relevance
“…Many studies have assessed quantity of exposure to each language using estimates by parents of relative quantity. Although this measure is second best, it is moderately to strongly correlated with word counts based on recordings and strongly related to concurrently obtained diary records of time exposed to English and Spanish . Most importantly, in many studies, caregivers’ estimates of children's relative quantity of exposure to each language significantly predict bilingual children's skill levels in each language .…”
Section: Effects Of Quantity Of Input On Bilingual Developmentmentioning
confidence: 96%
“…Many studies have assessed quantity of exposure to each language using estimates by parents of relative quantity. Although this measure is second best, it is moderately to strongly correlated with word counts based on recordings and strongly related to concurrently obtained diary records of time exposed to English and Spanish . Most importantly, in many studies, caregivers’ estimates of children's relative quantity of exposure to each language significantly predict bilingual children's skill levels in each language .…”
Section: Effects Of Quantity Of Input On Bilingual Developmentmentioning
confidence: 96%
“…However, there are other factors that could potentially attenuate across‐language correlations. For example, bilingual caregivers often have disparate levels of competencies in each of their home languages, or the quality of input may differ between languages for other reasons (Marchman, Martínez, Hurtado, Grüter, & Fernald, ). Furthermore, a measure of relative language exposure at home cannot account for differences in the amount of time children are exposed to each language in other arenas.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found caregiver estimates obtained in this way to be strongly related to diary‐based measures of the amount of time children are exposed to each language and to their skill levels in each language (Hoff et al., ). The estimates do not, however, capture differences in the density or quality of input, which also contribute to differences in children's language growth (Marchman, Martínez, Hurtado, Grüter, & Fernald, ).…”
Section: Methodsmentioning
confidence: 99%